“We Need to Live the World that is Possible”: Prefigurative Justice, Creative Collaboration, and the Activism of Rita Wong - Heather Smyth (Studies in Social Justice)
Although many writers and scholars struggle to cross the threshold between literary expressive culture and activism, poet Rita Wong has fostered and bridged both collaborative artistic and direct-action social justice work. Wong’s collaborations with Dorothy Christian, Larissa Lai, Cindy Mochizuki, and Fred Wah illuminate the promise of creative practice in confronting racial capitalism and climate destruction. This essay draws from the social movement theory of prefigurative politics, routed through abolition feminism and Indigenous place-based epistemology, to account for ethical consistencies between Wong’s poetics, collaborative artistic practice, and direct-action interventions. Prefigurative politics conveys “the embodiment, within the ongoing political practice of a movement, of those forms of social relations, decision-making, culture, and human experience that are the ultimate goal” (Boggs, 1977, p. 100). Wong’s work focuses on “Reckoning” at the pivot point of climate destruction: she writes, “our common survival depends on our collective ability to address the environmental devastation that has accelerated in this century, a devastation that will not end unless we learn to live by values that manifest and respect Indigenous relationships to the land and waters” (Wong, 2012, p. 535). Her scholarship and collaborative poetic engagements have attended to “Repairing” with words, performance, bodily engagement, and crafting a paradigm shift in alliance with human and nonhuman others, thinking with and through water. And Wong “Reworlds” through experimental and imaginative building of new relations, telling new stories. In keeping with prefigurative social movement practice, she and her collaborators act as if that new world has already arrived.